Preparation and Characterization of PEGylated Iron Oxide-Gold Nanoparticles for Delivery of Sulforaphane and Curcumin - Danafar, Hossein; Sharaﬁ, Ali; Askarlou, Sonia; Manjili, Hamidreza Kheiri (Drug Research, 2017)
Natural products have been used for the treatment of various diseases such as cancer. Curcumin (CUR) and sulforaphane (SF) have anti-cancer effects, but their application is restricted because of their low water solubility and poor oral bioavailability. To improve the bioavailability and solubility of SF and CUR, we performed an advanced delivery of SF and CUR with PEGylated gold coated Fe3O4 magnetic nanoparticles (PEGylated Fe3O4@Au NPs) to endorse SF and CUR maintenance as an effective and promising antitumor drugs. The structure of the synthesized nanocarrieris evaluated by, transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FT-IR). The results revealed that the size of NPs was 20 nm. They were mono-dispersed in water, with high drug-loading capacity and stability. CUR and SF were encapsulated into NPs with loading capacity of 16.32±0.023% and 15.74±0.015% and entrapment efficiency of 74.57±0.14% and 72.20±0.18% respectively. The in-vitro study of SF and CUR loaded PEGylated Fe3O4@Au NPs on human breast adenocarcinoma cell line (SK-BR-3) confirmed that cytotoxicity of SF and CUR can enhance when they are loaded on PEGylated Fe3O4@Au NPs in comparison to Free SF and void CUR. The results of flow cytometry and real-time PCR shown that nano-carriers can increase therapeutic effects of SF and CUR by apoptosis and necrosis induction as well as inhibiting of migration in SK-BR-3 cell line.
Keywords: sulforaphane; apoptosis; breast cancer; curcumin; PEGylated gold-coated Fe3O4 nanoparticles